Seroprevalence and risk factors associated with Salmonella Dublin presence in Algerian dairy farms - HEZIL, D; BENAMROUCHE, N; TENNAH, S; BENSEGHIR, H; ZAATOUT, N; ZAIDI, S; ZINEDDINE, R; BOUTABBA, DT; BELKADER, C; CHADI, H; BERNARD, C; GHALMI, F (Journal of the Hellenic Veterinary Medical Society, 2021)
Salmonella Dublin is a causative agent of a gastrointestinal bacterial infection prevalent in many cattle herds worldwide. Hence, the goal of this research was to evaluate the prevalence of Salmonella Dublin carriage in fecal and milk samples from dairy cattle from Algeria, and to investigate potential risk factors associated with the presence of S. Dublin antibodies. A total of 307 cows from 39 farms were analyzed in this study. Bacteriological and immunological methods were used to isolate and detect S. Dublin antibodies in feces and cow’s milk. Antimicrobial susceptibility testing was performed using the disc diffusion method. Logistic regression was used to study risk factors associated with S. Dublin antibodies. The bacteriological results showed the absence of S. Dublin and a prevalence of 0.97 % (3/307) (IC 95% 0 - 2.08)for S. Mbandaka. The immunological analysis of milk by the ELISA technique showed a prevalence of 36.33% (95% CI 30.44 - 42.22) for S. Dublin. Final multivariate regression models showed that the breed, the region and introduction of purchased cattle were associated with the presence of S. Dublin antibodies. This study is the first that reports the seroprevalence and risk factors associated with S. Dublin infection in Algeria and could be considered as a comparison point for further studies in Algeria.